Associations of blood pressure categories according to the 2017 American College of Cardiology/American Heart Association hypertension guideline and long-term blood pressure change with incident cardiovascular disease in middle-aged and elderly Chinese: the Dongfeng-Tongji cohort study. Issue 10 (October 2019) - Ma, Lin; Guo, Wenting; Yang, Liangle; Lai, Xuefeng; Fang, Qin; Liu, Miao; Yang, Huihua; Zhou, Lve; Wang, Hao; Xiao, Yang; He, Meian; Guo, Huan; et al.
Abstract : Objective: To assess the associations of newly defined blood pressure (BP) categories by the 2017 American College of Cardiology/American Heart Association guideline and changes in BP with the risk of cardiovascular disease (CVD) among the middle-aged and older Chinese. Methods: Among 29 086 participants aged 61.6 years from the Dongfeng-Tongji (DFTJ) cohort, we estimated the hazard ratio for CVD using Cox proportional hazard models. Results: As BP increased, we found a significant trend for greater risk of incident CVD, coronary heart disease (CHD) or stroke. Compared with the BP <120/<80 mmHg, those having stage 1 hypertension (BP of 130–139/80–89 mmHg) had an increased risk of CVD [hazard ratio of 1.29 (1.18–1.42)], CHD [hazard ratio of 1.27 (1.15–1.41)] and stroke [hazard ratio of 1.36 (1.10–1.70)], respectively. The effect of stroke was only presented in those aged at least 60 years, but not for those aged less than 60 years; whereas no age-specific association for CHD and CVD was found. Particularly, significantly increased risk of CVD (18%), CHD (14%) and stroke (37%) appeared even with elevated BP (120–129/<80 mmHg). Over a 5-year period, compared with individuals with stable BP less than 130/80 mmHg, those who maintained stage 1 hypertension had 43% increased risk for CVD, which was more prominent among those age at least 60 years. Relative to stable BP (−5 to 5 mmHg), a rise in SBP at least 15 mmHg and DBP at least 5 mmHg conferred 15 and 16% higher CVD risk; whereas the risk of CVD and CHD had 25 and 22% reduction with a decrease in SBP greater than15 mmHg, but not with DBP. Conclusion: Newly defined stage 1 hypertension and elevated BP were associated with increased risk of incident CVD, whereas long-term changes of SBP and DBP had effects of varying degree on CVD incidence. Abstract : Supplemental Digital Content is available in the text